Polystyrene microplastics mediate cell cycle arrest, apoptosis, and autophagy in the G2/M phase through ROS in grass carp kidney cells - Lu, Hongmin; Hou, Lulu; Zhang, Yue; Guo, Tiantian; Wang, Yu; Xing, Mingwei (Environmental toxicology, 2024)
Microplastics (MPs) have attracted widespread worldwide attention as a new pollutant. However, the role of reactive oxygen species (ROS) and cell cycle in nephrotoxicity induced by different concentrations of polystyrene microplastics (PS‐MPs) is unknown. This study used grass carp kidney cells (CIK) treated with different concentrations of PS‐MPs (0, 0.012, 0.0625, and 0.5 mg L−1) as subjects. With the increase of PS‐MPs concentration, the levels of ROS and malonaldehyde increased, while the level of total antioxidant capacity, superoxide Dismutase (SOD), and glutathione (GSH) activity decreased. The expression of BUB1 mitotic checkpoint serine/threonine kinase (BUB1), cyclin‐dependent kinase (CDK1), CDK2, CyclinB1, cell division cycle 20 homolog (CDC20), and B‐cell lymphoma‐2, sequestosome 1 decreased significantly. Nevertheless, the expression of Caspase 3, Cleave‐Caspase 3, cytochrome c (Cytc), BCL2‐associated X, apoptosis regulator, poly ADP‐ribose polymerase (PARP), Cleave‐PARP, Caspase 9, autophagy immunoblot kit (LC3), and Beclin1 increased. Our research shows that PS‐MPs can trigger oxidative stress and induce cell cycle arrest, apoptosis, and autophagy in CIK cells by regulating ROS. This work provides a theoretical basis for cellular biology and toxicology mechanisms and new insights into the potential risks to animals from MPs exposure in the environment.